Analysis of Health Policy Impacts on Adolescent Tobacco and Alcohol Consumption in ASEAN: An Ecological Descriptive Study - Hendriansyah, Marzalyla Putri; Setiawan, Syifa Azzahra; Putri, Sabrina Aprilia; Chusniati, Falah Nur; Maulida, Rizka (UI Scholars Hub, 2025)
The prevalence of tobacco and alcohol consumption among adolescents in Southeast Asia remains a public health concern despite the introduction of several national policies. This study assessed the relationship between policy implementation and consumption trends of tobacco and alcohol in selected ASEAN countries. Using a descriptive ecological design, we analyzed secondary data from the Global School-based Student Health Survey (GSHS) and policy documents from official government sources. We observed a rise in tobacco consumption in Indonesia (+4.2%) and Brunei (+5.5%), while Thailand experienced a slight increase (+0.3%). Conversely, alcohol consumption decreased marginally in Indonesia (-0.7%) and Brunei (-0.8%), but increased significantly in the Philippines (+4.1%) and Thailand (+5.2%). Policy impact is mediated by enforcement capacity, cultural norms, and socioeconomic factors, not policy existence alone. Further culturally adaptive, multi-sectoral approaches and regional cooperation are needed to reduce adolescent consumption.